THE EFFECTIVENESS CONTEXTUAL TEACHING AND LEARNING (CTL) METHOD TO SCIENCE RESULT STUDY FOR 8TH GRADE STUDENTS OF SMP NEGERI 12 YOGYAKARTA IN ACADEMIC YEAR 2014/2015. - Asih Murniati; Hidayati Hidayati; Tias Ernawati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2015)
The aims of this research was to know science resultÂ  study for 8th grade students of SMP Negeri 12 Yogyakarta by Contextual Teaching and Learning method and Conventional method. This research compared the diferences Science result study for 8th grade students of SMP Negeri 12 Yogyakarta by Contextual Teaching and Learning method and Conventional method. The research showed that science result study by Contextual Teahing and Learning method was high category than science result study by conventional method was medium category. The analyze showed that there was effect by using Contextual Teaching and Learning method to science result study for for 8th grade students of SMP Negeri 12 Yogyakarta in academic year 2014/2015.